Errors in oral presentations of Malaysian EAP students: an exploratory study - Muhamad, Ainon Jariah; Ahamad Shah, Mohamed Ismail; Engku Ibrahim, Engku Haliza; Abdul Ghani, Rozina (2011)
Thus this study aims to investigate the grammatical errors students made in the oral presentation tasks and to determine the types of grammatical errors according to misinformation, omission, addition, misordering and severe errors